2018
DOI: 10.1158/0008-5472.can-18-2225
|View full text |Cite
|
Sign up to set email alerts
|

An Interleukin-1 Signature in Breast Cancer Treated with Interleukin-1 Receptor Blockade: Implications for Treating Cytokine Release Syndrome of Checkpoint Inhibitors

Abstract: In this issue of Cancer Research, Wu and colleagues show that IL1b orchestrates tumor-promoting inflammation in breast cancer and can be targeted in patients using an IL1 receptor antagonist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 11 publications
0
24
0
Order By: Relevance
“…Administration of anakinra prevented breast cancer progression in humanized mouse model. Moreover, a pilot clinical trial wherein 11 patients with Her2 − metastatic breast cancer were treated with daily subcutaneous Anakinra for a median duration of 4 months, in combination with one of the standard chemotherapeutics, demonstrated that high risk Her2 − breast cancer patients would benefit from reducing levels of IL-1β and treatment with anakinra (45, 46). Excitingly, a recent phase three clinical trial (CANTOS) (45) demonstrated that an inhibitory antibody targeting IL-1β (canakinumab) could significantly reduce the incidence and mortality of lung cancer.…”
Section: Il-1βmentioning
confidence: 99%
“…Administration of anakinra prevented breast cancer progression in humanized mouse model. Moreover, a pilot clinical trial wherein 11 patients with Her2 − metastatic breast cancer were treated with daily subcutaneous Anakinra for a median duration of 4 months, in combination with one of the standard chemotherapeutics, demonstrated that high risk Her2 − breast cancer patients would benefit from reducing levels of IL-1β and treatment with anakinra (45, 46). Excitingly, a recent phase three clinical trial (CANTOS) (45) demonstrated that an inhibitory antibody targeting IL-1β (canakinumab) could significantly reduce the incidence and mortality of lung cancer.…”
Section: Il-1βmentioning
confidence: 99%
“…Wu et al analyzed 149 primary breast cancer tissues and found a correlation between overexpression of IL-1β, but not IL-1α, and breast cancer staging. IL-1β expression was mediated by malignant cell-membrane-associated TGF-β in dendritic cells (DC) and monocytes, and neutralizing TGF-β and IL-1β prevented cancer progression in humanized model mice [ 68 , 69 ]. Moreover, both IL-1β and IL-1RI were found to be upregulated in a cancer mouse model with bone metastases, and their blockage with anakinra decreased tumor size and metastases [ 70 ].…”
Section: Il-1 Dysregulation and Its Contribution To Cancer And Tumorimentioning
confidence: 99%
“…Both IL-1α and IL-1β activate the same IL-1 receptor, (a dimer of IL-1R1 and IL-1RAcP), while IL-1α is a membrane-bound protein and IL-1β is a soluble protein [36]. IL-1β promotes these effects through the activation of NFκB p65 and MAPK-ERK pathways, resulting in the release of cytokines [3740]. Similar to our published studies, which showed that OSM is important for osteolytic breast cancer metastasis to bone [19], IL-1β also stimulates the development of bone metastases [41].…”
Section: Introductionmentioning
confidence: 99%